Acetic acid D3 - H.P. Trommsdorf Institut Laue Langevin, 38042 Grenoble, France (My University, 2009)
Inelastic Neutron Scattering spectrum of Acetic acid D3, D₃COOH, measured on the TOSCA instrument.
Keywords: TOSCA